2014
DOI: 10.1007/s10554-014-0573-y
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of global longitudinal right ventricular function in patients with an acute inferior ST elevation myocardial infarction and proximal right coronary artery occlusion

Abstract: Right ventricular (RV) myocardial infarction (MI) is a frequent concomitant of an acute inferior MI. We set out to determine the diagnostic value of speckle tracking echocardiography in comparison with cardiac magnetic resonance (CMR) for RV stunning and scar prediction. 55 patients (66 ± 11 years) with an acute inferior ST elevation MI who underwent percutaneous coronary intervention (PCI) of an occlusion in the proximal right coronary artery were prospectively enrolled. An echocardiography was done on the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
6
0
4
Order By: Relevance
“…Hutyra et al constructed ROC curves to pedict RV scar by cardiac magnetic resonance imaging in IWMI patients and considered a cutoff value ≥ − 15.8% for RV peak systolic longitudinal strain (RV‐LS) with 92% sensitivity and 83% specificity for RV scar prediction (AUC: 0.93; P < 0.0001) and showed that RV‐LS was superior to TAPSE and TDI in determining the presence of RV scar …”
Section: Discussionmentioning
confidence: 99%
“…Hutyra et al constructed ROC curves to pedict RV scar by cardiac magnetic resonance imaging in IWMI patients and considered a cutoff value ≥ − 15.8% for RV peak systolic longitudinal strain (RV‐LS) with 92% sensitivity and 83% specificity for RV scar prediction (AUC: 0.93; P < 0.0001) and showed that RV‐LS was superior to TAPSE and TDI in determining the presence of RV scar …”
Section: Discussionmentioning
confidence: 99%
“…Оценка систолической функции ПЖ включает привычно используемые методики, такие как фракция изменения площади ПЖ (FAC), экскурсия трикуспидального кольца в М-режиме (TAPSE), систолическая скорость трикуспидального кольца в режиме импульсно-волнового тканевого Допплера (Sta) и новые технологии, основанные на оценке деформации стенки ПЖ (GlStRV). Наибольшее внимание в последние годы приковано именно к методике двухмерной деформации ПЖ (2D-STI), показавшей высокую точность в оценке сократительной способности ПЖ по сравнению с рутинно используемыми технологиями и позволяющей делать прогностическую оценку при СН [13,14]. Наконец, показатели деформации ПЖ могут использоваться для мониторинга его функции при назначении лекарственных препаратов, например, силденафила [15].…”
Section: Chambers Position Glstrv -Global Longitudinal Deformation Ounclassified
“…10 Similar results, provided by a meta-analysis of patients with inferior STEMI, associated RV involvement with adverse clinical events that were not due to more extensive infarction of the LV, but related rather to an increased propensity to develop life-threatening ventricular arrhythmias. 33 According to Hutyra et al, 34 35 Further prospective studies are needed to validate the ability of using RV strain to identify patients at a high risk for adverse outcomes.…”
Section: Potential Role Of Rv Strain In Evaluating Cardiovascular Dmentioning
confidence: 99%